Case Report : Diagnosis and Management of Peripartum Cardiomyopathy - Laksono, Sidhi; Puteri Nandifa, Veronica Nadya (UNUSA Press, 2023)
Introduction: Peripartum cardiomyopathy (PPCM) is generally viewed as diagnosis of exclusion in women presenting with heart failure and systolic dysfunction of unclear identifiable etiology. Etiology of PPCM is not fully understood and multifactorial. The purpose of this case is to review the diagnosis and management PPCM based on our experience in managing 31 years old woman with PPCM. Case: A 31 year old woman presented with dyspnea persisting for two days, exacerbated over the last 24 hours. She gave birth to her third child seven months ago. Patient had been experiencing dyspnea since 4 months earlier but seek no medical help. Upon physical examination, hemodynamic was stable, wet rales was noted in two thirds of the lung fields. Echocardiography revealed dilated left ventricle with eccentric hypertrophy and reduced ejection fraction (18%). Treatment was initiated with furosemide IV to resolve dyspnea, then Ramipril, bisoprolol, forxiga and spironolactone was given as heart failure therapy. Discussion: PPCM should be suspected in any peripartum women presenting with symptoms and signs of heart failure. Careful history taking and diagnostic testing especially echocardiography is important to help physicians determine the diagnosis. Conclusion: Treatment with medication adjusted for pregnancy and lactation may prevent adverse outcome, improve clinical symptoms and improve the overall cardiac functions. Long term follow up is important for patients with PPCM, since the optimal duration of medications after recovery is still unknown.